The emergence of Untraditional Islamic trends in Kazakhstan - Aktaulova, B. Zh. (Journal of Oriental Studies, 2016)
The author has examined the Modern religious picture in Kazakhstan. Also the external factors which impact on the emergence of Islamic radical currents were analyzed.